Polyhydroxyalkanoates (PHA)-based responsive polymers - Syed Mohamed, Syed Mohammad Daniel; Ansari, Nor Faezah; Md Iqbal, Nurhezreen; Anis, Siti Nor Syairah (Taylor & Francis Online, 2021)
Polyhydroxyalkanoates (PHA) envisage a potential biomaterial alternative to replacing synthetic polymers for their biodegradability and biocompatibility. Modification approaches exploit the attributes and adjust the intrinsic hydrophobic properties, such as blending to produce a new polymer mix with novel properties. Functionalization of PHA, especially chemical grafting, perform to introduce additional compounds covalently to PHA. As these methods address PHA potential and enable extensive utilization as a responsive material, reports are readily available in academia as confirmation. There are also substantial responsive PHA-based material applications in the biomedical area and agriculture materials, packaging materials, and nanocomposite materials.